Bob Marley, reggae, and rastafarians: its impact in the United States Society from the 60´s to the present - Estrella González, Lourdes Gabriela; Lofruscio Velástegui, Carla Tatiana
This thesis is about Reggae music, the Rastafari Movement and Bob Marley as a Reggae ambassador and how all these themes influenced the United States society from the 60´s to the present. The present investigation has been divided into four chapters. The first one shows the importance of Reggae music in the Jamaican culture, and how it reveals people sorrows caused by slavery, as well as their joys and emotions within their own reality. The second chapter refers to the Rastafarism, a religious, social, and political movement that foresees Haile Selassie I as the reincarnation of God. One relevant aspect about the Movement is its support of the use of Marijuana as a sacred herb. The third chapter is focused on the influence of an important man and singer, one of the greatest exponents of reggae music, the Jamaican singer, Robert Nesta Marley, considered an icon of the reggae musical genre. The fourth and last chapter is about the influence of the Rastafari Movement and Reggae music in the U.S society from the 60´s to the present. This investigation was based on bibliographical research and surveys to Americans